2009
DOI: 10.1063/1.3073860
|View full text |Cite
|
Sign up to set email alerts
|

Reduced nonthermal rollover of wide-well GaInN light-emitting diodes

Abstract: Nonthermal rollover (or efficiency droop) of the electroluminescence (EL) efficiency has been investigated for near-UV-emitting (AlGaIn)N single-well light-emitting diodes (LED) with varying GaInN well widths grown on substrates with different dislocation densities (DDs). For each DD the well width of the mesa-LEDs has been optimized for maximum EL efficiency at high operating currents. LEDs on freestanding GaN (DD 4 x 10(exp 7) cm-2) with an 18 nm thick GaInN wide-well active region show the highest efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 14 publications
4
37
0
Order By: Relevance
“…. This is especially helpful for the design of thick quantum wells or double heterostructure devices to mitigate the effects of the efficiency droop [2]. Limited availability of large-scale freestanding nonpolar GaN wafers as well as their high price favours the heteroepitaxial growth on foreign substrates.…”
mentioning
confidence: 99%
“…. This is especially helpful for the design of thick quantum wells or double heterostructure devices to mitigate the effects of the efficiency droop [2]. Limited availability of large-scale freestanding nonpolar GaN wafers as well as their high price favours the heteroepitaxial growth on foreign substrates.…”
mentioning
confidence: 99%
“…Further details on epitaxy and LED structure can be found in Ref. [5]. In the following, we concentrate, without loss of generality, on LEDs grown on ULD templates due to space limitations.…”
Section: Contributedmentioning
confidence: 99%
“…Gardner et al [4] reported a delayed onset of the efficiency droop for LEDs with a double-heterostructure or wide well (WW) active region instead of narrow QWs, leading to higher maximum QE reached at high driving currents. Recently, Maier et al [5] provided evidence that combining the WW active region concept with growth on low defect density substrates is a promising approach to overcome the efficiency reduction at high driving currents at least for near-UV (about 400 nm) LEDs. In this paper, we present a detailed study of the carrier density dependent QE and carrier recombination times of such LEDs, from which a model is derived based on the interplay between defect assisted recombination, depending on dislocation density, and strongly carrier density dependent loss processes.…”
mentioning
confidence: 99%
“…One established solution is the use of thick InGaN QWs. [8][9][10] However, because of rapidly decreasing material quality of thick indium-rich InGaN films, no improvement over state-of-the-art multi-QW (MQW) LEDs could be shown. Alternatively, the active-layer carrier density can be reduced by enabling MQW operation.…”
Section: Figure 2 Emission Power Versus Current Density For a Green-mentioning
confidence: 99%